Perspektif Al-Qur’an Tentang Sel Saraf Dalam Kajian Integrasi Agama Dan Sains - Siti Nafilatul Rohmah; Kholisatul Umami; Ifka Ramadhani; Siti Andini; Alfina Wildatul Fitriyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Humans are God's perfect creation. Perfection lies in reason. Apart from intelligence, humans also have a brain as the control center for all human activities. The aim of this research is to examine and discover more deeply about human nerve cells from the perspective of the Koran. This research uses qualitative methods and produces descriptive data through a literature approach. The main sources start from secondary sources including books or journals related to the concept of nerve cells according to religious and scientific views. There are several verses scattered in the surahs of the Koran regarding nerve cells. The word